PREREQUISITES AND METHODS OF STRATEGIC INFLUENCE OF BRANDS ON CONSUMER BEHAVIOR AND FORMATION OF BRAND STRATEGY - Chepelenko, Anzhelika (European Science, 2025)
Researching consumer behavior, forming such behavior and influencing it is one of the key topics of branding, especially in the formation of brand strategies.Understanding that consumer behavior can be both irrational and rational, we understand that ap